13 Elective Breast Surgery (Plastic Surgery Oral Board Prep, 2019)
This chapter will review elective breast surgery, including breast reduction, augmentation, and mastopexy. The reader will be able to manage the large breast, the small breast, and assess and address complications.
Keywords: macromastia; micromastia; reduction mammoplasty; breast reduction